Sistem Monitoring Aktivitas Anak Berbasis Web menggunakan Model Rapid Application Development (RAD) pada TK Islam Terpadu Qurrata A'yun - Hasan, Hastrid; Arifin, Rohayati; Pato, Markani; Hidayat, Febri; Nasir, Khaedir Rahman; Wisda; Asnimar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The problem that occurs in TKIT Qurrata A'yun is that currently it only uses WhatsApp Groups as a means of communication between teachers and parents to convey information about children, including activities outside school, Records of children's learning progress are only submitted to parents when receiving report cards. With the web-based system, access to information and monitoring children's learning activities becomes more practical, allowing parents to view data directly from various devices such as computers, laptops, or mobile phones, anytime and from anywhere if they are connected to the internet. The purpose of this study is to design a monitoring system that can provide information to parents, implement a web-based child learning monitoring system. These data were obtained through interviews and observations. The system development method used is Rapid Application Development with 3 stages, namely needs planning, user design, and implementation. The results showed that the success rate of 84.7% of parent questionnaires and 92.5% of teacher questionnaires, indicated that the planned system was